Implementasi Sistem Real Time untuk Pendeteksi Dini Banjir berbasis ESP8266 dan Weather API - Shandi Sonna Mahardika; Wijaya Kurniawan; Fariz Andri Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Flood is when the volume of water continues to increase and then inundate the surrounding land. Flooding occurs when the intensity of rain is high. To anticipate flooding, it is necessary to have an information system that in real time provides information on flood status. Internet of things or IoT can send, receive, and process flood information. The flood early warning system applies Weather API, HC-SR04 sensor, FC-37 module, and YF-S201 sensor. The sensor and Weather API on the system must be able to work together. RTOS or real time operating system provides multitasking and scheduling features to run multiple programs simultaneously. With the RTOS task on the system can be scheduled based on its priority. Virtuino is an Android-based application whose job is to display flood warnings and status. The system test results is sensor FC-37 and YF-S201 has a percentage error of 0%, the FC-37 Module can measure rainfall intensity according to its limits, the Weather API has a percentage of weather reading errors of 13%, all tasks are executed with an average of 8996.75ms and does not exceed the time limit, and the Virtuino Application takes 2.3 seconds to access and display the flood status.